Moments of Truth: An Empirical Analysis of Indian Consumers - Trivedi, Arti; Suri, Beenu; Mishra, Saurabh; Mishra, Pratika (Indian Journal of Marketing, 2011)
This paper is an attempt to reveal the consumer's perception about the point when they take their purchasing decision and form a relationship with a particular product or/and service. They can form an impression before purchasing, during purchasing, after purchasing, or even after experiencing the same. These Moments of Truth are the critical and sensitive points when consumers actually decide whether they will purchase a product/service again or not. These touch points can be human, static and interactive interactions that mix together to create such impressions. Unfortunately, if a marketer fails to satisfy a customer upon even one Moment of Truth, it will completely eliminate the customer's memory of good service. On the other hand, getting it right can erase all the wrongs that the customer has experienced previously.